Social Economy and the Transition Towards Circular Economy: a Survey Based Approach - Gorgon, Mihaela Ioana; Bercea, Oana Bianca; Păcurariu, Roxana Lavinia; Boscoianu, Mircea (Dr. Viktor Koval, 2024)
Introduction. European social economy employment is 6.3% of the European Union's (EU) working population. In Romania and other recent EU member states, it is responsible for less than 2% of the total employment. The need for a precise legal and political concept of social economy and social enterprise confused the Romanian population and made their measurement easier. Both concepts have been increasingly employed in Romania since 2005, following the new EU policy approaches for social inclusion. Consequently, the social economy has grown significantly in recent years, with a diverse range of actors pursuing various social goals. Aim and tasks. The paper aims to provide an up-to-date overview of the social economy in Romania by showing the activity types and their involvement in the circular economy transition and then by examining the social enterprises' social and economic performance. Results. The creation of social value and social impact of social enterprises, the response of organisations to entrepreneurial change, and the level of risk-taking were substantiated. The way these aspects are correlated with performance was determined. A quantitative analysis of the social economy and transition towards a circular economy in Romania yielded the following main findings: i) more than half of the surveyed enterprises did not understand the concept of a circular economy, and ii) there was a strong statistically significant correlation (R=0.61) between social performance and environmental receptivity. The correlation between social and economic performance is statistically significant, with an average intensity (R=0.32). The correlation between economic performance and responsiveness to the environment was also statistically significant for medium-to-high intensity (R= 0.28). Conclusions. The social economy puts social and democratic objectives into practice, whereas a circular economy is essential for a sustainable transition. Various actors operate in different industries and geographic areas in the Romanian social economy. Social economy actors aim to contribute to a more inclusive economy and equitable society, inspiring the government and private sector to demonstrate and implement more inclusive and sustainable practices. These practices cover decent labour, more education, and secure lives. Social innovation, defined as long-term solutions to social problems, is a critical way to build a circular society.